Aspek Hukum Paralegal Sebagai Pemberi Bantuan Hukum Terhadap Masyarakat Miskin Dan Marginal Dalam Mencari Keadilan - Maria Rosalina (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Indonesia is a legal state or recthsstaat and not a state of power (machtsstaat). To solve legal problems, someone deserves to get legal aid and one of the legal aids is from paralegal. Paralegal is a non-law graduate but possesses basic knowledge and understanding of law and human rights to provide legal assistance to the needy. The term paralegal in the Indonesian legal system is, in writing, just recognized and mentioned in the law on legal aid No. 11 of 2016, in Article 9 and Article 10. Keywords: Legal Aspect, Paralegal, Legal Aid